Smart Bin / Nurul Shahrina A Ghapar ... [et al.] - A Ghapar, Nurul Shahrina; Ismail, Nawwar Najwa; Abdullah, Nur Syakirah; Mohamad, Siti Norbaya (2019)
The product to be developed is SMART BIN. This product is built with many features that would be a helpful towards both consumer and our environment. The bin aids people in automatically segregate the garbage and make process of waste disposal much easier. Disposal in this situation was meant to be the process taken after waste separation or segregation of garbage take place and this process account of a government. The concepts is to create a product that can be a helpful in handling Waste produce everyday. Smart sensors are installed for automatically open the lid and automatically help with the segregation of the waste while compressor is installed to compress or compact the garbage so that it can lowering the level and gives more space. Both features are considered as the unique features of this product.